Battery management systems. Volume II, - Plett, Gregory L. (Artech House, 2016)
This second volume discusses state-of-the-art applications of equivalent-circuit models as they pertain to solving problems in battery management and control. Readers are provided information on how to use models from Volume I to control battery packs, along with discussion of fundamental flaws in current approaches. In addition, Volume II introduces the ideas of physics-based optimal battery controls and explains why they can be superior to the state-of-the-art equivalent-circuit controls. Publisher abstract.
Keywords: Electric batteries.; elektronické knihy; electronic books